Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/fractalfract6010022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Composition of Fine Aggregate on the Frictional Behavior of Concrete–Soil Interface under Sulfuric Acid Environment

Abstract: Through direct shear tests, this paper aimed to research the effect of fine marble aggregate on the shear strength and fractal dimension of the interface between soil and concrete corroded by sulfuric acid. More realistic concrete rough surfaces than the artificially roughened surfaces were formed by immersing four concrete plates in plastic buckets filled with sulfuric acid for different periods of time. The sand was adopted to imitate the soil. 3D laser scanner was employed to obtain the digital shapes of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…Fractal theory is a new method of mathematics, resolving the irregularities in nature [67][68][69][70]. Many researchers [71][72][73][74][75][76][77][78] demonstrated that fractal theory links microstructures with the macro-performance of cement-based materials well, and vice versa.…”
Section: Fractal Dimension Calculationmentioning
confidence: 99%
“…Fractal theory is a new method of mathematics, resolving the irregularities in nature [67][68][69][70]. Many researchers [71][72][73][74][75][76][77][78] demonstrated that fractal theory links microstructures with the macro-performance of cement-based materials well, and vice versa.…”
Section: Fractal Dimension Calculationmentioning
confidence: 99%
“…We obtain the fractal dimension [37][38][39]. of concrete crack images by taking the logarithm of both sides of the Equation (2), as described in Equation (3).…”
Section: Fractal Dimension Of Concrete Crack Imagementioning
confidence: 99%
“…It can be used for PCSBs to reduce the dead load, save costs in bridge maintenance, prolong service life, and improve structural behavior. In addition, high-strength concrete has a high uniform density and very low impermeability, which is conducive to the durability of concrete buildings [23,24]. Few experimental results have been reported in the literature on the shear behavior of PHCSBs with compressive concrete strength exceeding 55 MPa, especially about the combined use of dry joints and external tendons.…”
Section: Introductionmentioning
confidence: 99%